An aspartic protease of the scabies mite Sarcoptes scabiei is involved in the digestion of host skin and blood macromolecules. - Wajahat Mahmood; Linda T Viberg; Katja Fischer; Shelley F Walton; Deborah C Holt (Public Library of Science (PLoS), 2013)
BACKGROUND: Scabies is a disease of worldwide significance, causing considerable morbidity in both humans and other animals. The scabies mite Sarcoptes scabiei burrows into the skin of its host, obtaining nutrition from host skin and blood. Aspartic proteases mediate a range of diverse and essential physiological functions such as tissue invasion and migration, digestion, moulting and reproduction in a number of parasitic organisms. We investigated whether aspartic proteases may play role in scabies mite digestive processes. METHODOLOGY/PRINCIPLE FINDINGS: We demonstrated the presence of aspartic protease activity in whole scabies mite extract. We then identified a scabies mite aspartic protease gene sequence and produced recombinant active enzyme. The recombinant scabies mite aspartic protease was capable of digesting human haemoglobin, serum albumin, fibrinogen and fibronectin, but not collagen III or laminin. This is consistent with the location of the scabies mites in the upper epidermis of human skin. CONCLUSIONS/SIGNIFICANCE: The development of novel therapeutics for scabies is of increasing importance given the evidence of emerging resistance to current treatments. We have shown that a scabies mite aspartic protease plays a role in the digestion of host skin and serum molecules, raising the possibility that interference with the function of the enzyme may impact on mite survival.